Pengelolaan Pembangunan Infrastruktur Kalurahan Pacarejo Kapanewon Semanu Kabupaten Gunungkidul - Bella Nata Syah; Supardal Supardal (CV. Ulil Albab Corp, 2023)
Infrastructure development in village areas is an important part of national development. Since the issuance of Law No. 6/2014 on Villages, villages have the authority to manage and organize their government and territory. One of the village's tasks is to carry out development in order to improve the community's economy and improve the standard of living of the village community and advance the village. Kalurahan Pacarejo is a Kalurahan attached to Kapanewon Semanu, Gunung Kidul Regency. The Kalurahan has a very large area and has twenty-four (28) padukuhan. In this case, the Pacarejo Village Government cannot carry out infrastructure development in all padukuhans in the same year. Moreover, with a very minimal budget to carry out infrastructure development in all hamlets. This makes the Pacarejo Village Government must be able to have a strategy in infrastructure development so that the development carried out is appropriate and has potential that can be developed and has a positive impact on the Village government and the Pacarejo Community. With these problems, researchers are interested in focusing on this research with the title. Pacarejo Village Government Strategy in Infrastructure Development in Pacarejo Village, Kapanewon Semanu, Gunung Kidul Regency